SINERGITAS PENYELENGGARA PEMILU DALAM PENGAWASAN PEMILIHAN BUPATI DAN WAKIL BUPATI TAHUN 2015 DI KABUPATEN INDRAGIRI HULU - Munawaroh "; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In law constitution number 15 0n 2011 clause 1 paragraph 5, that: election effectuation is an institution which organize the election consist of General Election Commissions and Election Supervisory Agency as a unity with election effectuation function to choose member of the House of Representatives, Regional Representative Council, Regional People’s Representative Assembly, President and Vice President, directly selected by public, also for governor, regent and vice regent democratically. When Simultaneous Local Election on December 9th 2015, Indragiri Hulu district becoming one of district that held election of Regent and Vice Regent. The result of election showed that the pair number 2 are H. Yopi Arianto , SE and H. Khairizal, SE, Msi won the election. In the opposite side they felt unsatisfied and incongruity in the process of election, so they submit a lawsuit about the result of the election to Constitutional Count. In the demanding pair number 1 showed some proves of infraction which are administrative infraction, code of ethics infraction, and criminal offense infraction. The purpose of the research is to get to know the effectuation sinergity in election regulatory control of Regent and Vice Regent in 2015 at Indragiri Hulu district. Thie research uses qualitative approach with descriptive research type, data collection by interview and documentation. The research is held in Indragiri Hulu district. The result of this research in the effectuation sinergity in election regulatory control of Regent and Vice Regent in 2015 at Indragiri Hulu district is awareless well. This could be seen from coordination and communication of election organizer that less effective to anticipate in the steps of election preparation so causes election infraction and the finishing mechanism that less of firm from the organizer. The obstacles that be found is less human source who obey the rule and communication. Keywords: Synergy, Supervisor